Optimization of Pancreatic Lipase Inhibition in Fermented Beverages Brewed from Katuk Leaves Using RSM - Yati Maryati; Agustine Susilowati; Hani Mulyani; Aspiyanto Aspiyanto; Setyani Budiari (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
The inhibition of pancreatic lipase and the associated reduction of lipid absorption has become the most appropriate approach for treating obesity. Meanwhile, katuk (Sauropus androgynus) leaves are rich in polyphenols that act as natural bioactive compounds and are also responsible for the potential effect on metabolic diseases, including inhibition of pancreatic lipase activity. Naturally occurring polyphenols can inhibit pancreatic lipase and consequently affect fat digestion as well as energy intake. Therefore, this study aimed to optimize the inhibitory activity of pancreatic lipase, which plays an essential role in lipid absorption. In fermented katuk (Sauropus androgynus) leaves were brewed following RSM using a Box Behnken design. Data analysis was used to optimize the formulation with a response surface model consisting of three factors namely sucrose concentration ranging from 10-20% b/v, culture 10-20 b/v, as well as fermentation time of 1-5 days. The parameters tested were the percentage inhibition of pancreatic lipase, antioxidant activity, polyphenol, and total acid. Based on the RSM optimization results obtained from the three influencing factors, the optimum conditions were established namely 10.43% w/v sucrose, 10% v/v kombucha culture, and fermentation for 5 days. These conditions yielded the most optimal responses, with the percentage inhibition of pancreatic lipase, antioxidant activity, polyphenol, and total acid being 86.13%, 96.27%, 0.97 mg GAE/mL, and 1.11%, respectively. In general, the results demons-trated that the RSM method of the Box Behnken design and the parameter prediction values obtained using the model equation are in good agreement with the experimental values with at least R2 ≥ 0.8.